Stability Analysis of Electric Power Systems Using Controllers Facts on Transmission System - Vinda Sri Mulyani H; Siti Anisah; Zuraidah Tharo (Sean Institute, 2025)
Power system stability is a critical factor in maintaining the continuity and quality of energy supply, especially in transmission systems that face load fluctuations and integration of renewable energy sources. The main problems in this study are voltage instability and reactive power oscillations that often occur due to disturbances such as sudden load changes or short circuits, as well as the limited capacity of conventional controllers in reducing these impacts. This study aims to explore the role of Static VAR Compensator (SVC) as part of Flexible AC Transmission Systems (FACTS) technology in improving transmission system stability through a qualitative approach. The research method is carried out with descriptive analysis based on literature studies, mathematical modeling of the power system, and numerical simulations to understand the dynamics of the system response to disturbances. The focus is given to qualitative evaluation of the interaction between SVC, system parameters (voltage, reactive power, and phase angle), and the impact of controller placement on network reliability. Simulation case studies cover small to large disturbance scenarios to assess the effectiveness of SVC in restoring stability. The results show that SVC integration makes a significant contribution to improving the dynamic stability of the transmission system. Qualitative analysis finds that SVC is able to reduce voltage oscillations and accelerate post-disturbance system recovery through adaptive reactive power regulation. However, the limited capacity of SVC in handling extreme disturbances indicates the need for combination with other FACTS controllers (such as STATCOM or UPFC) for more complex systems. This study also reveals the importance of proper SVC placement strategy to optimize its effectiveness.